The effects of neoadjuvant chemoradiotherapy and an in-hospital exercise training programme on physical fitness and quality of life in locally advanced rectal cancer patients (The EMPOWER Trial): study protocol for a randomised controlled trial. Issue 1 (December 2016) - Loughney, Lisa; West, Malcolm; Kemp, Graham; Rossiter, Harry; Burke, Shaunna; Cox, Trevor; Barben, Christopher; Mythen, Michael; Calverley, Peter; Palmer, Daniel; Grocott, Michael; Jack, Sandy
Abstract Background The standard treatment pathway for locally advanced rectal cancer is neoadjuvant chemoradiotherapy (CRT) followed by surgery. Neoadjuvant CRT has been shown to decrease physical fitness, and this decrease is associated with increased post-operative morbidity. Exercise training can stimulate skeletal muscle adaptations such as increased mitochondrial content and improved oxygen uptake capacity, both of which are contributors to physical fitness. The aims of the EMPOWER trial are to assess the effects of neoadjuvant CRT and an in-hospital exercise training programme on physical fitness, health-related quality of life (HRQoL), and physical activity levels, as well as post-operative morbidity and cancer staging. Methods/Design The EMPOWER Trial is a randomised controlled trial with a planned recruitment of 46 patients with locally advanced rectal cancer and who are undergoing neoadjuvant CRT and surgery. Following completion of the neoadjuvant CRT (week 0) prior to surgery, patients are randomised to an in-hospital exercise training programme (aerobic interval training for 6 to 9 weeks) or a usual care control group (usual care and no formal exercise training). The primary endpoint is oxygen uptake at lactate threshold ( V · o 2 $$ \overset{\cdotp }{V}{o}_2 $$ at θ ^ L $$ {\widehat{\uptheta}}_{L} $$ ) measured using cardiopulmonary exercise testing assessed over several time points throughout the study. Secondary endpoints include HRQoL, assessed using semi-structured interviews and questionnaires, and physical activity levels assessed using activity monitors. Exploratory endpoints include post-operative morbidity, assessed using the Post-Operative Morbidity Survey (POMS), and cancer staging, assessed by using magnetic resonance tumour regression grading. Discussion The EMPOWER trial is the first randomised controlled trial comparing an in-hospital exercise training group with a usual care control group in patients with locally advanced rectal cancer. This trial will allow us to determine whether exercise training following neoadjuvant CRT can improve physical fitness and activity levels, as well as other important clinical outcome measures such as HRQoL and post-operative morbidity. These results will aid the design of a large, multi-centre trial to determine whether an increase in physical fitness improves clinically relevant post-operative outcomes. Trial registration ClinicalTrials.govNCT01914068 (received: 7 June 2013). Sponsor: University Hospital Southampton NHS Foundation Trust.